Regional Peculiarities of Gender Policy in the Republic of Belarus - Flura I. Khramtsova (Проблемы постсоветского пространства, 2017)
The essence of the state gender policy at the present stage in the Republic of Belarus is substantiated. The regional peculiarities of the implementation of the state program document «The National Plan of Action for Ensuring Gender Equality for 2017-2020» are disclosed. The experience of designing a regional plan for the implementation of the state gender policy of the Minsk City Executive Committee for 2017-2020 is shown on the example of the Academy of Management under the President of the Republic of Belarus. In the broad sense, gender policy is understood as one of the strategic directions of social policy. At the same time, gender policy is aimed at overcoming discrimination based on gender, gender asymmetry in the sphere of power relations, gender imbalance in the labor market, employment. Gender policy in the context of international legislative acts takes into account the national identity, the features of the political system, and the socio-economic development of a concrete state. With all existing differences, gender policy in its narrow meaning is a purposeful, dynamic, adaptive process of public administration, regulation, coordination, control in the sphere of gender relations on three bases: political doctrine; state ideology; program priorities and values of gender equality. The interdisciplinarity of gender policy integrates it with other areas of social policy. Thus, gender policy is implicit in goals, the content of state family policy, demographic, educational, youth, protection of maternity and childhood . Formation and implementation of gender policy is based on analysis, interpretation of statistical data (social policy directions), which are disaggregated by sex, in the dynamics of indicators. Based on the UN used methodology, taking into account the national speciﬁcs of the Belarusian society, has been created relevant gender statistics and it is developing as an information resource for decision-making. Gender statistics in Belarus are used by authorities, practitioners-managers and scientists. Practice conﬁrms that the use of a gender approach in public administration contributes to the procuring of the women rights, freedoms, and opportunities. It increases their social and political statuses both within societal institutions and at the state level. Conversely, ignoring the gender factor can be devastating for society and its institutions.